The Last Days - Moll, James (Spielberg, Steven ; Shoah Foundation, 1998)
Including newly-discovered historical footage and a rare interview with a former Nazi doctor at Auschwitz, the film tells the story of five people, born in Hungary as they return from the United States to their hometowns and to the ghettos and concentration camps in which they were imprisoned.